2001
DOI: 10.1159/000048055
|View full text |Cite
|
Sign up to set email alerts
|

Proteases from <i>Vipera lebetina </i>Venom Affecting Coagulation and Fibrinolysis

Abstract: Our studies of the venom from the Levantine viper Vipera lebetina have demonstrated the existence of both coagulants and anticoagulants in the same venom. We showed that V. lebetina venom contains: (1) proteases that degrade fibrinogen, but not fibrin; (2) fibrinolytic enzyme (lebetase); (3) factor X activator (VLFXA); (4) factor V activator (VLFVA). Fibrinolytic enzyme and VLFXA are metalloproteases; the other studied enzymes are serine proteases. α-Fibrinogenase has no homolog among known serine proteases. β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…However, cleavage at Arg 1545 , which is adjacent to the AR, must have a significant impact. Support for this comes from the longstanding observation in the field that cleavage of FV by a protease in Russell's viper venom at Arg 1545 results in full activation (7,13,(15)(16)(17)(18)(19)(20). Due to the nature of how the PRR inhibits cofactor function, it is likely that there are multiple ways in which FV could be activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cleavage at Arg 1545 , which is adjacent to the AR, must have a significant impact. Support for this comes from the longstanding observation in the field that cleavage of FV by a protease in Russell's viper venom at Arg 1545 results in full activation (7,13,(15)(16)(17)(18)(19)(20). Due to the nature of how the PRR inhibits cofactor function, it is likely that there are multiple ways in which FV could be activated.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, these studies found that variable amounts of cofactor activity are observed depending on which region of the B-domain is cleaved and which assay is used to evaluate activity. A clear consensus is that maximal activity correlates with cleavage at Arg 1545 (7,13,(15)(16)(17)(18)(19)(20)(21)(22). Although these studies have advanced the field, such correlative studies have not provided mechanistic insight into how FV activation unfolds.…”
mentioning
confidence: 99%
“…However, in most of them, proteolytic enzymes, phospholipase activities, and other factors may account for their destructive effects on muscle tissue (13,14), as only one of 33 tested venoms entirely inhibited interaction of ␣ 7 ␤ 1 integrin with its laminin ligands. In addition to abundant phospholipase activity and numerous proteases (14,17), the venom of V. lebetina contains two disintegrins (lebein-2 and lebein-1) that inhibit ␣ 7 ␤ 1 integrin binding to its laminin ligands. In this study, we have established and optimized their purification from the crude toxin and have characterized their integrin-inhibiting function.…”
Section: K Dmentioning
confidence: 99%
“…Being abundant in most snake venoms, phospholipase A 2 is mainly responsible for myotoxic effects (13,14). Various proteases of snake venoms specifically cleave blood-clotting factors or components of the ECM, thus resulting in bleeding dysfunctions and tissue necrosis (15)(16)(17).…”
mentioning
confidence: 99%
“…While there are enzymes that cause hypofibrinogenemia, hypoprothrombinemia, thrombocytopenia and fibrinolysis; at the same time, there are potent proteases (e.g. arginine esterase and hydrolase) acting as activators of coagulation factors X and V, thereby promoting coagulation (7). In addition, enzymes -such as hyaluronidase -damage connective tissues, leading to enhanced toxin dissemination.…”
Section: Discussionmentioning
confidence: 99%